PENGARUH SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION DAN DAMPAKNYA PADA REUSE INTENTION BUS PARIWISATA DI KOTA SURABAYA - Zinedine, Jonathan; Claudia, Rania; Remiasa, Marcus (Catholic University Musi Charitas, 2023)
This research is conducted to examine the influence of Service Quality and Customer Satisfaction on Reuse Intention on Tourism Bus in the City of Surabaya (Study on: Surabaya Heritage Track Bus). The questionnaire is distributed to 92 respondents that lived in Surabaya and Outside Surabaya and have used Surabaya Heritage Track Bus more than once. The type of research is casual research that using Partial Least Square analysis method - Structural Equation Model (PLS-SEM). The result shows that Service Quality has a significant effect on Customer Satisfaction, and Customer Satisfaction has a significant effect on Reuse Intention. Meanwhile, Customer Satisfaction has a mediating role from Service Quality to Reuse Intention.